(untitled) (Publicaciones en Ciencias y Tecnología, 2019)
Radioactivity as a physical phenomenon has brought benefits and mistakes to the scientific world and to humanity. Its discovery mainly attributed to Antoine Henri Becquerel, Marie Sklodowska-Curie and Pierre Curie, whom at the end of the 19th century observed and classified the elements and radioactive isotopes uranium, thorium, polonium and radio. These elements in their natural state ionize the air around them and are capable of producing enormous quantities of energy, hence their application in nuclear power plants. In the international year of the periodic table, it is appropriate to remember the work of Marie Sklodowska-Curie, who dedicated her life to studies on radioactivity; even she died because of exposure to it without protection. The present paper is dedicated to her memory, a brief biography and her scientific contributions, the effects questioned by the use of radioactive isotopes, some history about radioactivity, and its relationship with the periodic table of the elements.